Preparation of xyloglucan-grafted poly(N-hydroxyethyl acrylamide) copolymer by free-radical polymerization for in vitro evaluation of human dermal fibroblasts - Maykel González-Torres; Ricardo Martínez-Mata; Erika Karina Ruvalcaba-Paredes; Alicia del Real; Gerardo Leyva-Gómez; Alfredo Maciel-Cerda (Journal of Materials Science: Materials in Medicine)
Abstract Xyloglucan is a rigid polysaccharide that belongs to the carbohydrate family. This hemicellulose compound has been widely used in biomedical research because of its pseudoplastic, mucoadhesive, mucomimetic, and biocompatibility properties. Xyloglucan is a polyose with no amino groups in its structure, which also limits its range of applications. It is still unknown whether grafting hydrophilic monomers onto xyloglucan can produce derivatives that overcome these shortcomings. This work aimed to prepare the first copolymers in which N-hydroxyethyl acrylamide is grafted onto tamarind xyloglucan by free-radical polymerization. The biocompatibility of these structures in vitro was evaluated using human dermal fibroblasts. Gamma radiation-induced graft polymerization was employed as an initiator by varying the radiation dose from 5–25 kGy. The structure of the graft copolymer, Xy-g-poly(N-hydroxyethyl acrylamide), was verified by thermal analysis, Fourier transform infrared spectroscopy, and nuclear magnetic resonance spectroscopy. The findings indicate that the degree of grafting and the cytotoxicity/viability of the xyloglucan-based copolymer were independent of dose. Notably, the grafted galactoxyloglucan exhibited efficient support for human dermal fibroblasts, showing heightened proliferative capacity and superior migration capabilities compared to the unmodified polymer. This copolymer might have the potential to be used in skin tissue engineering.